Technology in farming: Unleashing farmers' behavioral intention for the adoption of agriculture 5.0. - Nitesh Mishra; Nabin Bhandari; Tek Maraseni; Niranjan Devkota; Ghanashyam Khanal; Biswash Bhusal; Devid Kumar Basyal; Udaya Raj Paudel; Ranjana Kumari Danuwar (PLoS ONE, 2024)
The agriculture sector has undergone a remarkable revolution known as Agriculture 5.0 (Ag 5.0), emphasizing digital technology to boost efficiency and profitability of farm business. However, little is known about farmers' behavioral intension to adopt Ag 5.0. In this study we examine factors influencing farmer's behavioral intension for Agriculture 5.0, identify implementation obstacles and provide managerial solutions to promote Ag 5.0 in Madhesh Province, Nepal, using the Technology Acceptance Model (TAM) and Structural Equation Model (SEM). We tested total of 20 different hypotheses. Primary data were collected from 271 farmers across 9 municipalities in Saptari District, Nepal. The study reveals that technology anxiety [(β = 0.101, p<0.01); (β = 0.188, p<0.01)], self-efficacy [(β = 0.312, p<0.01, (β = 0.170, p<0.05)] and social influence [(β = 0.411, p<0.01), (β = 0.170, p<0.05)] significantly impact the perceived usefulness as well as perceived ease of use, respectively. Individual innovativeness also affects the perceived usefulness (β = 0.004, p<0.05) and perceived ease of use (β = 0.281, p<0.01). Moreover, the study found that attitude towards using Ag 5.0 is significantly influenced by perceived usefulness (β = 0.083, p<0.10) and ease of use (β = 0.189, p<0.01), which, in turn, affects the intention to use Ag 5.0 (β = 0.858, p<0.01). Farmers perceive training programs, government assistance, and subsidies as helpful in overcoming challenges associated with adopting Ag 5.0. This study provides valuable insights for policymakers, development partners, and farmers' organizations, enabling them to understand the factors influencing the readiness for Ag 5.0 adoption in Nepal.